5 - Espace public et participation politique en Afrique : le cas de l’Algérie - Moulai-Hadj, Mourad (Africa Development, 2021)
The year 1989 marked a new phase in the political lives of nations, follow- ing the fall of the Berlin Wall and the end of ideological conflicts between the two former antagonistic poles. This change led to a new way of transforming state structures and articulating their role in reforming the public space. The example of the events of October 1988 in Algeria con- stitutes an experience of the appearance of a new public space that boosted political and associational life, with the advent of the multiple party system and electoral pluralism. This experience of democratization created a dynamic public space, with associational movements, a new citizenship, a new form of management of political conflicts and a new political culture. Data from the field1 on the participation of Oranese youth in the public space, and their political attitudes, will help back up the approach developed in this article.